(untitled) (Research, Society and Development, 2021)
Introduction: The world is currently experiencing a pandemic situation, caused by the VIRUS SARS-CoV-2, causing the Coronavirus, Educational activity has been undeniably affected in learning processes and teaching, educational institutions, at this time, have chosen to use strategies of teaching activities remotely. Objective: to identify the technological tools used by higher education teachers during the pandemic period. Method: This was a descriptive-exploratory research of quantitative approach, carried out with professors from a State University located in the Southern Region of Brazil. Results: Among the training to teach online, 71.6% (n=58) report not having received it and 28.3% (n=23) reported having received, among the 23 who received training, 17 highlight that they do not consider it sufficient to perform online activities. Conclusion: It is highlighted as fragility that few teachers used platforms for online classes and tools for video editing, which is reflected, how these classes are actually being conducted, as well as the lack of preparation of teachers regarding the didactics adopted through these tools.